A Case of Parkinson’s Disease with No Lewy Body Pathology due to a Homozygous Exon Deletion in Parkin - Krisztina Kunszt Johansen; Sverre Helge Torp; Matthew J. Farrer; Emil K. Gustavsson; Jan O. Aasly (Case Reports in Neurological Medicine)
Parkinson’s disease (PD) is a clinical diagnosis based on the presence of cardinal motor signs, good response to levodopa, and no other explanations of the syndrome. Earlier diagnostic criteria required autopsy for a definite diagnosis based on neuronal loss in the substantia nigra pars compacta (SNpc) and the presence of Lewy bodies and neurites. Here, we present a patient who developed parkinsonism around the age of 20, with an excellent response to levodopa who, at age 65, received bilateral STN deep brain stimulation (DBS). The patient died at age 79. The autopsy showed severe neuronal loss in the SN without any Lewy bodies in the brainstem or in the hemispheres. Genetic screening revealed a homozygous deletion of exon 3-4 in the Parkin gene. In this case report we discuss earlier described pathological findings in Parkin cases without Lewy body pathology, the current diagnostic criteria for PD, and their clinical relevance.